Maravilha e conhecimento de Tasso a Vico Meraviglia and knowledge in Italian literature from Tasso to Vico - Erminia Ardissimo; Silvana Scarinci (Per Musi, 2011)
É um lugar comum associar o Barroco à meraviglia. Depois de contemplar o verso de Marino, è del poeta il fin la meraviglia, meu ensaio discutirá as concepções poéticas de Tasso, as quais unem o maravilhoso e a verossimilhança dentro do enquadramento da religião (ou seja, como uma representação do sobrenatural). A formulação de Tasso de que tudo que faz sentido é verdadeiro é discutida aqui em referência aos episódios amorosos de seu poema Jerusalem liberada. O ensaio abordará os escritos teóricos de Francesco Patrizi, que em seu Deca Ammirabil define o poeta como criador do maravilhoso, e também abordará o Cannocchiale Aristotelico de Emanuele Tesauro. O maravilhoso no século XVII também é uma característica dos escritos de Galileu, tanto como um traço da natureza das coisas, como uma manifestação da genialidade dos seres humanos na descoberta e invenção. A conclusão do ensaio enfoca a Scienza Nuova de Vico. It is a commonplace to associate Baroque and meraviglia. After having placed Marino's verse, è del poeta il fin la meraviglia, my paper will discuss Tasso's poetic conceptions, which unite the marvelous and the verisimilar within the framework of religion (that is to say as a representation of the supernatural). Tasso's statement that all that is meaningful is true, is discussed here referring to love episodes in his poem, Jerusalem Delivered. The paper will deal with the theoretical writing of Francesco Patrizi, who in his Deca Ammirabili defines the poet as a creator of the marvelous, and it will also deal with the Cannocchiale Aristotelico by Emanuele Tesauro. The marvelous in the Seventeenth century also characterizes Galileo's writings, both as a feature of the nature of things and as a manifestation of the geniality of human beings in discovery and invention. The outcome of the paper is Vico's Scienza Nuova.